The use of lower formalin-containing embalming solution for anatomy cadaver preparation (Medical Journal of Indonesia, 2012)
Background: We used cadaver embalming technique with a high concentration of formaldehyde (37% formaldehyde). However, it gives toxic effects which can endanger the technicians, lecturers and students. For that reason, the effective, efficient and safer embalming process is needed; in this article we describe the use of low formalin solution (5-7.5% formaldehyde) to achieve prior purposes. Methods: Cadaver is embalmed by actively pumping low formalin-containing solution (5-7.5%) via femoral arteries. Further methods are detailed in this manuscript. Results: Paler cadaver with more intact and easier to dissect specimen (drier and still moist with no fungal growth) was resulted by using this low formalin technique. Conclusion: The use of low formalin-containing solution in cadaver embalming gave good quality results for anatomy teaching. (Med J Indones. 2012;21:203-7)